Bureaucratic and societal determinants of female-led microenterprises in India - Devlina; Santosh Kumar Sahu (Administrative Sciences, 2023)
This study examines the barriers to female entrepreneurship in India's microenterprise sector through society and bureaucracy. The study uses grammatical genders in languages to capture the societal attitudes towards female entrepreneurship. Using a probit model, it was found that states where the spoken language is two-gendered, have poor representations of women in entrepreneurial positions compared with states with languages that are multi-gender or no gender. It is further argued that these societal attitudes also reflect through people in power, such as bureaucrats, credit managers, bankers, etc., which affects female entrepreneurship. The paper finds empirical evidence for the grease-the-wheel hypothesis, i.e., in the presence of a discriminating inefficient business ecosystem, women entrepreneurs use non-market strategies such as corruption to alter decisions in their favour. Thus, an effort to reduce corruption at an immature stage, when these societal institutions have not yet developed, might cause more harm than benefit.
Keywords: D73; J16; L26; Z13; 350; corruption; female entrepreneurship; grammatical genders; India; language; microenterprises